Panduan Meningkatkan Visibilitas Produk di Shopee Melalui Optimasi Kata Kunci Judul Produk - Hakim, Widarta Muhammad Fais Rahman; Setiawardani, Maya (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
In the face of increasingly fierce competition on the Shopee e-commerce platform, effective strategies are crucial for online stores to remain competitive. This guide examines the implementation of an SEO optimization strategy during an internship program at Company XYZ to enhance product visibility and traffic, focusing on stores in the fashion industry. The activities include identifying underperforming products, conducting relevant keyword research through competitor analysis and market trends, and optimizing product titles. The results indicate that well-executed SEO optimization can significantly boost product exposure without relying on paid promotions. However, evaluating the success of product visibility requires considering various factors beyond keyword optimization in product titles. This initiative also highlights the importance of regular monitoring and analysis of search trends and competitors to ensure the long-term relevance of SEO strategies. The findings from this activity are expected to provide practical guidance for Shopee store owners, particularly in the fashion market, in optimizing their product performance amidst intense competition.